2020
DOI: 10.1177/2042753019900963
|View full text |Cite
|
Sign up to set email alerts
|

Understanding learner participation at scale: How and why

Abstract: Understanding learner participation is essential to any learning environment to enhance teaching and learning, especially in large scale digital spaces, such as massive open online courses. However, there is a lack of research to fully capture the dynamic nature of massive open online courses and the different ways learners participate in these emerging massive e-learning ecologies. To fill in the research gap, this paper attempted to investigate the relationship between how learners choose to participate in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…The majority of the international students perceived participation and interaction, meeting individual needs, aiding better understanding, and providing better explanation during online teaching to be less effective than in-class teaching, which could be because the online classes were during a unique period when the teachers and learners were under environmental pressures. Thus, this result supports (Haniya & Paquette, 2020) that motivations and barriers are factors that influence participation and interaction in online classes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The majority of the international students perceived participation and interaction, meeting individual needs, aiding better understanding, and providing better explanation during online teaching to be less effective than in-class teaching, which could be because the online classes were during a unique period when the teachers and learners were under environmental pressures. Thus, this result supports (Haniya & Paquette, 2020) that motivations and barriers are factors that influence participation and interaction in online classes.…”
Section: Discussionsupporting
confidence: 81%
“…In enhancing teaching and learning processes, learners' participation is essential (Haniya & Paquette, 2020). The study by Haniya and Paquette (2020) examined learners' massive online course participation, using participation patterns such as "Advanced, Balanced, Early, Limited, and Delayed Participation", and found two major factors that drive learners' participation (motivations and barriers), and their impacts vary with respect to the learners.…”
Section: Learner's Participation and Engagement In Technology-enhanced mentioning
confidence: 99%
“…Some authors tried to understand innovative pedagogies and the factors that affect the performance of learners. This may help us in a near future, especially after this pandemic period, in order to organize and orientate the education of the next generation with help of these professors (Haniya & Paquette, 2020;Hill & France, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Variations in motivation, including its types and strength, have been found to associate with different learning patterns and outcomes in MOOCs (Zheng et al, 2015). For example, Haniya and Paquette (2020) found that highly active learners were more often motivated by clear learning goals, such as enhancing professional skills and preparing for a future career, while learners with limited participation were more often motivated by the interest to gain general knowledge. Semenova (2020), investigating 10,187 learners in nine MOOCs, concluded that learners driven by their general interest and the intention of getting a certificate of completion were more likely to finish the course, whilst learners registered for access to the course materials were less likely to do so.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coursera added 10 million users within 2 months (from mid‐March to mid‐May 2020), seven times more than the previous year (Lohr, 2020). However, the openness of MOOCs gives rise to the challenge of devising appropriate pedagogies to suit a learner body heterogeneous in multiple ways: age, geographical location, employment status, educational attainment, skillset, and learning pattern (Haniya & Paquette, 2020).…”
Section: Introductionmentioning
confidence: 99%